Impact of reduced light intensity on wheat yield and quality: Implications for agroforestry systems - Jia, Jiyu; Xu, Meng; Bei, Shuikuan; Zhang, Hongzhi; Xiao, Li; Gao, Yonghong; Zhang, Yongqiang; Sai, Lihan; Xue, Lihua; Lei, Junjie; Qiao, Xu (Agroforestry systems, 2021)
In China, agroforestry is a traditional practice that diversifies agricultural production and enhances natural resource utilization; however, it create competition for light between trees and understory crops due to heterogeneous spatio-temporal light patterns, and can lead to systemic reductions in grain yield as shade increases. The present study simulated reductions in light intensity caused by walnut trees ( Juglans regia L.) before budburst, between budburst to tree foliage expansion, and after foliage expansion, to examine the effects on wheat ( Triticum aestivum L.) yield and quality in an agroforestry system. We designed artificial shading systems using black polyethylene screen of varying density (21 %, 44 and 74%reductions in light intensity) at the jointing (approximately 70 d of shading), booting (approximately 55 d of shading), and anthesis (approximately 40 d of shading) stages, with full solar radiation (S0) as a control. Reduced light intensity significantly decreased the number of fertile florets per spike, resulting in a marked decline in grains per spike. Decreased light intensity also significantly decreased photosynthetic rates, grain yield and associated components (spike number, grains per spike, and thousand-grain weight), Furthermore, when applied at the anthesis stage, shading had the strongest negative impact on wheat productivity via decreases in thousand-grain weight. Decreased light intensity substantially enhanced grain and stalk nitrogen concentrations, as well as protein and wet gluten contents. However, the increase in grain quality did not compensate for the decreased final grain yield. Our evaluation of the effect of heterogeneous spatio-temporal light patterns on wheat yield and quality via an artificial shade system may help plantation managers to optimize agroforestry practices in Southern Xinjiang, Northwest China.